2011
DOI: 10.1038/onc.2011.53
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Clara cell-mediated homeostatic inflammation is involved in lung metastasis

Abstract: We have previously shown that tumor necrosis factor (TNF)a produced from primary tumor-induced expression of two endogenous Toll-like receptor 4 (TLR4) ligands, S100A8 and serum amyloid A3 (SAA3), in pre-metastatic lungs. However, mechanistic details of the signaling network and relevance to pulmonary physiology are poorly understood. Here, we identify Clara cells as a control tower of the network. Clara cell ablation by naphthalene suppressed pulmonary recruitment of CD11b þ TLR4 þ cells and spontaneous lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 41 publications
1
43
0
2
Order By: Relevance
“…Importantly, various changes which facilitate metastasis have been described in the lung. These pre-formed lung niches encompass cells recruited from the bone marrow and resident cells such as club/Clara cells152 and alveolar macrophages153. Factors produced by resident cells in metastatic niches can enhance the survival and outgrowth of disseminated tumour cells.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, various changes which facilitate metastasis have been described in the lung. These pre-formed lung niches encompass cells recruited from the bone marrow and resident cells such as club/Clara cells152 and alveolar macrophages153. Factors produced by resident cells in metastatic niches can enhance the survival and outgrowth of disseminated tumour cells.…”
Section: Resultsmentioning
confidence: 99%
“…29 The auto-amplification of SAA3 in lung-specific Club cells may contribute to organotropism in lung metastasis. 43 We more recently reported that SAA3 activates TLR4/MD-2 pathway in a MyD88-dependent, but TRIF-independent manner by using an SAA3 peptide. 28 In contrast, in case of S100A8, RAGE and TLR4 are identified as S100A8/A9 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Collected cells were incubated with anti-CD11b-FITC and anti-Gr-1-PE Abs. The recruitment of CD11b + Gr-1 + cells in the lungs was determined by flow cytometry, as described previously (12). All procedures performed with mice were approved by the Animal Research Committee of Tokyo Women's Medical University.…”
Section: /2mentioning
confidence: 99%
“…An anti-SAA3 neutralizing Ab inhibited lung metastasis. The autoamplification of SAA3 by lung-specific Clara cells may contribute to organotropism in lung metastasis (12).…”
mentioning
confidence: 99%